Composite Nasoseptal Flap for Palate Reconstruction. Issue 7 (October 2019) - Gadkaree, Shekhar K.; Feng, Allen L.; Sharon, Jeffery D.; Richmon, Jeremy D.; Emerick, Kevin S.; Lin, Derrick T.; Deschler, Daniel G.; Varvares, Mark A.; Pipkorn, Patrick; Zenga, Joseph
Abstract : Abstract: Palatal fistulae represent a pathological connection from the oral cavity through the hard or soft palate to the nasal cavity and can present a significant reconstructive dilemma. Surgical correction of palatal fistulae is often limited by prior treatment, including ablative procedures and radiotherapy, or previous reconstructive attempts. In light of these challenges, the nasoseptal flap represents an excellent adjacent source of vascularized tissue which may be suitable for palatal fistula repair with minimal donor site morbidity, low associated risks, and a short recovery period. The purpose of this study was to fully understand the potential utility of this reconstructive option, including the ability to harvest a composite flap including both septal cartilage and contralateral mucoperichondrium. In this single institution prospective study consisting of a series of 5 cadaver dissections, primary outcome measures were the anterior reach of the flap as compared to the anterior nasal spine and the size of the palatal defect that the nasoseptal flap could be used to successfully reconstruct. Composite flaps were successfully harvested in continuity with a disc of septal cartilage and contralateral mucoperichondrium, providing structural integrity to the reconstruction and the ability to anchor the flap to the native hard palate mucosa. The nasoseptal flap's maximum anterior reach was within 2.0 cm (standard deviation of 0.1 cm) from the anterior nasal spine and could reliably reconstruct palate defects of 2.5 cm or less. The nasoseptal flap provides a viable regional option for reconstructing defects of the hard palate. Prospective clinical trials are needed to investigate long-term reconstructive and functional outcomes of the composite nasoseptal flap in palatal reconstruction.